Impact of psychological gender on competition performance of elite female boxers - Osipov, A.; Kudryavtsev, M.; Galimova, A.; Kolokoltsev, M.; Romanova, E.; Lazarova, M. (Journal of Physical Education and Sport, 2023)
Sport professionals declare a significant interest increase of females about classes which are considered "male" sports traditionally: weightlifting and various combat sports. The investigation of gender-specific features of female's motivation to classes of masculine sports is an actual problem of sports psychology. The purpose of this research is determine the impact of psychological gender on competition performance of elite female athletes in amateur boxing. Material and Methods. Elite female athletes (n=82) who practicing amateur boxing, participated in this research. The diagnosing the psychological gender (method by O. Lopukhova) and analysis of competition scores of athletes in recommendations with guidelines of the German potential analysis system (PotAS) were performed. Results. There were founded that most of female participants (n=35) have the predominance of masculine psychological gender. Other part of female participants (n=32) have the predominant features of androgynous psychological gender and some female athletes (n=15) have been identified as feminine type of psychological gender. In meantime, there were no reliable differences in total number of athletes between female boxers, who have masculine or androgynous psychological gender. Participants, who have feminine psychological gender, have a significant (p = 0.05) younger chronological mean age, than other female athletes. There were significant (p = 0.05) differences in competition scores between participants, who have feminine psychological gender and other female athletes. Female boxers, who have feminine psychological gender, demonstrated a significant (p = 0.05) lower competition scores, than other participants. In their body, a significantly lower content of the muscle component was established, compared with the male and androgynous psychological gender. In meantime, there were no reliable differences in competition scores among participants, who have masculine or androgynous psychological gender. Conclusions. This investigation suggested that there is reliable impact of psychological gender on competition performance of female boxers, regarding female athletes with feminine psychological gender. Female athletes, who have feminine psychological gender, demonstrated a significantly lower competitions result, than female boxers, who have masculine or androgynous psychological gender. In meantime, there were no reliable effects of psychological gender on competition performance of female athletes, who have masculine or androgynous psychological gender.